Communicative Competence of Early Childhood Islamic Education Students: The Synergy between Islamic Pedagogy and Modern Communication Studies - Suprayitno, Kabul; Hassan, Fauziah; Yekti, Sanjaka; Ahmadi, Ahmadi (Al-Ishlah: Jurnal Pendidikan Islam, 2025)
Background:Recent scholarship highlights communicative competence as a foundational dimension of teacher professionalism; however, within Islamic Early Childhood Education, its conceptualization remains fragmented, often limited to surface-level linguistic or performative skills. This narrow treatment obscures the ethical, dialogic, and digital dimensions necessary for cultivating educators capable of navigating contemporary pedagogical demands while remaining grounded in Islamic value frameworks. Research Objectives:This study investigates the multidimensional constitution of communicative competence among prospective Islamic early childhood teachers and seeks to theorize an integrative framework, Islamic Educommunication Competence—that synthesizes spiritual–moral ethics, dialogic interaction, and critical digital literacy. Methods: Using an interpretivist qualitative design, data were collected from 60 participants through semi-structured interviews, sustained classroom observations, and document analysis of teaching artifacts. A hybrid inductive–deductive thematic analysis was applied, supported by iterative coding validation and intercoder reliability to ensure analytic rigor. Results: The analysis reveals that communicative competence emerges through three interdependent domains: (1) ethical–spiritual orientation, characterized by adab, sincerity, and moral intentionality; (2) dialogic and sociocultural mediation, reflected in collaborative reasoning, reflective discourse, and contextual sensitivity shaped by local Islamic cultural practices; and (3) critical digital engagement, which enables ethical, multimodal, and audience-responsive communication. Together, these domains articulate a theoretical expansion of communicative competence beyond linguistic ability. Conclusions: The study advances a conceptual model of Islamic Educommunication Competence that repositions communicative ability as an ethical–dialogic construct embedded within digital ecologies. This model offers significant implications for teacher education curricula seeking to integrate Islamic ethics with contemporary communication practices. Future research should examine the model’s transferability across broader Islamic education contexts and its empirical impact on classroom outcomes.